Biologically Active Ajuga Species Extracts Modulate Supportive Processes for Cancer Cell Development - Rauca, Valentin-Florian; Vlase, Laurian; Casian, Tibor; Sesarman, Alina; Gheldiu, Ana-Maria; Mocan, Andrei; Banciu, Manuela; Toiu, Anca (Frontiers in Pharmacology, 2019)
Backround: Ajuga species have been used in traditional medicine for their diuretic, anti-inflammatory, wound-healing and hepatoprotective properties. Purpose: The phytochemical profile and anticancer potential of three Ajuga sp. (A. genevensis, A. chamaepitys, and A. laxmannii) from Romania was investigated. Materials and methods: The phytochemicals were extracted from the aerial parts of Ajuga sp. by using different solvents and methods. The hydroalcoholic extracts were examined for total phenolic, flavonoid and iridoid contents, and HPLC/MS was used to analyze the polyphenolic compounds and iridoids. The phytochemical profile was also evaluated by principal component analysis in connection with antitumor efficacy of extracts. The antiproliferative potential was evaluated using the ELISA BrdU-colorimetric immunoassay. Western Blot with regard to inflammatory protein NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) p65 subunit production expression in cell lysates was performed. Quantification of oxidative stress marker malondialdehyde (MDA) was determined by high-performance liquid chromatography (HPLC). Enzymatic and non-enzymatic antioxidant capability was assessed by measuring catalase activity and by evaluating the total antioxidant capacity (TAC) of treated cells. Results: A. laxmannii ethanol extract showed the highest total phenolic and flavonoid content, while A. genevensis ethanol extract was more abundant in iridoids. The overall cytostatic effect of the investigated plant extracts was exerted through strong inhibitory actions on NF-κB, the key molecule involved in the inflammatory response and via oxidative stress modulatory effects in both murine colon carcinoma and melanoma cell lines. Conclusions: A. laxmannii showed the most significant antitumor activity and represents an important source of bioactive compounds, possibly an additional form of treatment alongside conventional anticancer drugs.